2006
DOI: 10.1111/j.1475-1305.2006.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Evaluation of Mixed‐mode Stress Intensity Factors Utilizing Digital Image Correlation

Abstract: A method for determining mixed‐mode stress intensity factors from displacement fields obtained by digital image correlation is studied. To perform automatic evaluation, not only stress intensity factors but crack‐tip location, higher‐order terms in the series expansion of displacement fields and rigid‐body displacement components are also determined simultaneously using nonlinear least squares based on the Newton–Raphson method. Experimental results show that the mixed‐mode stress intensity factors are evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(108 citation statements)
references
References 12 publications
2
104
0
2
Order By: Relevance
“…Some early analyses used leastsquares methods to fit the Williams' series to the DIC results, and obtained the mode I SIF [32]. The method has also been extended to mixed mode loading [33][34][35][36][37]. However, the leastsquares technique is quite sensitive to accurate definition of the crack tip location, as highlighted by McNeill [32].…”
Section: Introductionmentioning
confidence: 99%
“…Some early analyses used leastsquares methods to fit the Williams' series to the DIC results, and obtained the mode I SIF [32]. The method has also been extended to mixed mode loading [33][34][35][36][37]. However, the leastsquares technique is quite sensitive to accurate definition of the crack tip location, as highlighted by McNeill [32].…”
Section: Introductionmentioning
confidence: 99%
“…4. Parhizgar et al [10] reported a similar result for quasi-static fracture of glass fiber/epoxy system. Rowlands [11] also reported increasing critical stress intensity factor with increasing angle, but the trend was not an exponential variation possibly due to the multidirectional composite laminates he has studied.…”
Section: Discussionmentioning
confidence: 57%
“…he experimental characterisation of crack tip fields is normally done using surface techniques such as photoelasticity [1], Moiré interferometry [2], thermo-elastic stress analysis [3], electronic speckle pattern interferometry [4] or digital image correlation [5,6]. For thin components, the surface behaviour is normally representative of the T complete behaviour [7].…”
Section: Introductionmentioning
confidence: 99%